My mother, the mermaid chaser - Hoang, Jamie Jo (Crown Books, 2025)
Told in alternating voices, sixteen-year-old Paul travels to Vietnam where he searches for more information about his mother, who made the difficult decision to leave her children after a long struggle with grief and an abusive marriage.